Effects of varied rest time interval between sets to failure using bench press in competitively trained athletes - Kwek, Shaun Seng Erng (2019)
Background: Different training goals have different recommended rest time intervals (RTI). The attainment of these training goals depends on the ability to maintain the number of repetitions over a consecutive set within a prescribed zone. RTI may determine the effectiveness of executing multiple set program. Purpose: To examine the rate of recovery between three sets of bench press to failure in competitively trained athletes (CTA). Method: 18 males (age 23.2 ± 1.1 years old; height 170.8 ± 5.1 cm; body weight 70.3 ± 5.4 kg) and 18 females (age 22.3 ± 1.1years old; height 157.8 ± 3.8 cm; body weight 59.8 ± 5.9 kg) completed a day of briefing and 1-Repetition Maximum (RM) bench press test on the and enrolled in a randomized control trial over three sessions. For each session, they will perform three sets of bench press to volitional failure with a randomly assigned rest time interval (RTI) of 2-, 3-, or 4-minutes between sets. Results: There is significant difference between all sets and all RTI (p<.001). Difference between set 1 and set 2, set 2 and set 3, and set 1 and 3 is significant across all RTI (p<.001). The highest decrement in repetitions occurred in the 2-minute RTI. Conclusion: 2-, 3-, and 4-minute RTI periods are insufficient even for CTA to recover in time in order to replicate the number of repetitions over consecutive sets.